From one place to another: forced mobilities and collective displacements in the Hispano-Visigoth kingdom of Toledo (6th-7th centuries) - Frighetto, Renan (Romanitas - Revista de Estudos Grecolatinos, 2017)
The mobilities, whether individual or collective, draw the attention of the Historian regardless of the space-time clipping he analyzes. In fact, the mobilities are directly related to both the long-term process and to the set of facts and events linked to disputes in a given socio-political and economic environment. In this sense, the world of Late Antiquity can be characterized as the world of mobilities, whether they be large groups represented by the barbarian populations that settled in the interior of the orbis romanorum, were those motivated by personal interests and wants or by political problems that led the individual out of his original sociopolitical environment. The latter, which we can characterize as forced mobilities, involved multiple forms of withdrawal from everyday sociopolitical coexistence that could be both voluntary and involuntary and have some interesting examples in the Hispano-Visigothic kingdom of Toledo of the sixth and seventh centuries.
Keywords: Forced mobility; Collective displacements; Hispano-Visigothic Kingdom of Toledo; Late Antiquity